Multimode Extraction from Dielectric Loaded Waveguides via Method of Moments - (:unkn) unknown (IEEE, 2017)
Multimodal interactions for inhomogeneously loaded rectangular waveguide are examined. Method of Moments (MoM) is utilized to obtain the scattered field data. Validation of the approach is performed by comparison with mode matching technique.
Keywords: generalized scattering matrix; method of moments; rectangular waveguide